Differential effects of grape juice on gastric emptying and renal function from cisplatin-induced acute adverse toxicity. (August 2016) - Ko, J-L; Tsai, C-H; Liu, T-C; Lin, M-Y; Lin, H-L; Ou, C-C
Grape skin and seeds contain large amounts of phytochemicals such as polyphenols, resveratrol, and proanthocyanidins, which possess antioxidant activities. Cisplatin is widely used in the treatment of cancer. High doses of cisplatin have also been known to produce acute adverse effects. The aim of this study was to investigate the protective effects of antioxidant properties of whole grape juice (with skin and seeds) on cisplatin-induced acute gastrointestinal tract disorders and nephrotoxicity in Wistar rats. Gastric emptying is significantly increased in whole grape juice-pretreated rats when compared to cisplatin treatment alone. The expression of ghrelin mRNA of stomach is increased in rats with whole grape juice. However, pretreatment with whole grape juice did not reduce renal function markers in acute renal toxicity. No significant changes were recorded in the oxidative stress/antioxidant status parameters of any study group. In contrast, pretreatment with whole grape juice slightly improved tubular cell vacuolization, tubular dilatation, and cast formation in renal tubules. These results show that consumption of whole grape juice induces somewhat beneficial effects in preventing cisplatin-mediated dyspepsia but does not offer protection against cisplatin-induced acute renal toxicity.